Kids, cartoons, and cookies: Stereotype priming effects on children's food consumption. Issue 2 (17th June 2015) - Campbell, Margaret C.; Manning, Kenneth C.; Leonard, Bridget; Manning, Hannah M.
Abstract: In studies with adult participants, exposure to a prime that activates a stereotype can lead to stereotype‐consistent behavior. Given significant differences in cognitive development, stereotype formation, and use of stereotypes from early childhood to adulthood, the emergence of such behavioral priming effects in childhood is uncertain. To begin addressing whether children exhibit behavioral priming effects from stereotype exposure, we conduct three experiments in which children are exposed to either a normal weight or overweight cartoon character prime, and subsequently (as an unrelated activity) have access to high energy, low‐nutrient food. Our results with children from 6 to 14 years old indicate that overweight cartoon character primes can activate the overweight stereotype, leading to relatively high levels of food intake. This effect persisted when participants were simultaneously exposed to a normal weight and an overweight character together (study 2), and was successfully moderated by the activation of health knowledge (study 3).